A Facile and Efficient Method to Fabricate Highly Selective Nanocarbon Catalysts for Oxidative Dehydrogenation. Issue 2 (21st December 2016) - Zhang, Yajie; Wang, Jia; Rong, Junfeng; Diao, Jiangyong; Zhang, Jiayun; Shi, Chunfeng; Liu, Hongyang; Su, Dangsheng
Abstract: Carbon nanotubes (CNTs) were used in oxidative dehydrogenation (ODH) reactions. Quinone groups on the CNT surface were identified as active sites for the dehydrogenation pathway. Liquid‐phase oxidation with HNO3 is one way to generate various oxygen functionalities on the CNT surface but it produces a large amount of acid waste, limiting its industrial application. Here, a facile and efficient oxidative method to prepare highly selective CNT catalysts for ODH of n ‐butane is reported. Magnesium nitrate salts as precursors were used to produce defect‐rich CNTs through solid‐phase oxidation. Skeleton defects induced on the CNT surface resulted in the selective formation of quinone groups active for the selective dehydrogenation. The as‐prepared catalyst exhibited a considerable selectivity (58 %) to C4 olefins, which is superior to that of CNTs oxidized with liquid HNO3 . Through the introduction of MgO nanoparticles on the CNT surface, the desorption of alkenes can be accelerated dramatically, thus enhancing the selectivity. This study provides an attractive way to develop new nanocarbon catalysts. Abstract : Effective defects : The solid‐phase oxidation of carbon nanotubes (CNTs) with magnesium nitrate salts is a promising method to create highly selective CNT catalysts for the oxidative dehydrogenation (ODH) of n ‐butane. The defects generated on the CNT surface, which are susceptible to in situ oxidation into quinone groups in the ODH reaction, promote the selectivity and yield to alkenes. Additionally, the introduction of MgO nanoparticles could facilitate the desorption of alkenes and improve the selectivity.